PENGARUH TERPAAN KONTEN YOUTUBE JAYNE ALEXANDER TERHADAP PERILAKU KONSUMERISME FANDOM BLINK (Survei Terhadap Grup Chat Blink Berbagi di Telegram) - Indah Lestari (2023)
This research examines youtube media exposure to consumerism, exposure is the intensity of the public situation where a person or group is exposed to message spready by the media. The purpose of this research to find out the magnitude of the influence Jayne Alexander's youtube content exposure to blink fandom consumerism behavior. The Theory used in this study is the Uses and Effect theory developed by Svan Windahl which is applied to media use the how media effects the audience. This Uses and Effect Theory explains the relationship between mass communication conveyed through mass media has an effect on users. The sample used in this study is random sampling, this research method uses a quantitative approach with a descriptive type of research in collecting this research data using a questionnaire that was addressed to 100 respondents.